PENGARUH TEMPERATUR MESOFILIK TERHADAP LAJU ALIRAN BIOGAS DAN UJI NYALA API MENGGUNAKAN BAHAN BAKU LIMBAH KOLAM IKAN GURAME - Dwi Irawan; Kemas Ridhuan (TURBO [Tulisan Riset Berbasis Online], 2016)
The reserve lack of fossil fuels as a source of energy in contrast to increasing the energy demand growth as human populations, especially in indonesia. Biogas as renewable energy environmentally friendly could be one of solutions to current permasalah energy. Biogas produced with the help of bacteria metanogen or metanogenik. Biogas produced by take waste farm will bring value more. Waste management done with better than it can prevent the environmental pollution also provide added value of business cattle or the cultivation of fish. If dirt shaped mud and it is not so levels soon cleared ammonia in the water would rise and can threaten survival ikan-ikan preserved. The purpose of this study is to find influence temperature mesofilik against the rate of flow of biogas and hasill flame biogas. The method do first is preparing equipment for making a series of using drigen biogas, with varying temperature that 300C mesofilik, 350C, 400C. The result showed, the rate of flow of treatment t1 biogas 736,8 ml/day, as for treatment t2 the rate of flow of biogas 774,8 ml/day, and treatment t3 the rate of flow of biogas 748,75 ml/day and potential biogas 1,8719 ml / liters of raw materials with the same pressure on all the treatment 101.570,25 N/m2. The fiery show results flame blue biogas resulting from all treatment.The result showed treatment temperature impact on the rate of flow of biogas and results flame biogas.